Climate change impacts on rainfed agriculture in the Guadiana riverbasin (Portugal) - Valverde, Pedro (2015)
In this study, the crop yield response of rainfed crops to climate change was evaluated focusing on themost representative crops in the Guadiana river basin. The quantification of crop yields was performedusing a simple soil water balance model framework. The herbaceous crop yields were evaluated with theISAREG model, implementing a water balance approach combined with the Stewart method. A similarwater balance approach was used to estimate the yields for the most representative permanent rain-fed woody crops in the region using an alternative spreadsheet-based model, but implementing a moredetailed water stress evaluation through the crop cycles. Yields were simulated for two future periods(2011–2040) and (2041–2070) using, as climate inputs, temperature and precipitation series, reflecting acombination of five climate change scenarios (CCS) created using the ensemble-delta technique appliedto CMIP3 climate projections datasets to represent different alternative climate change bracketing con-ditions for rainfall and air temperature. The results showed that comparatively with the reference periodclimate (1961–1990) rainfed crop yields will decrease in future period 1 (2011–2040) and reach evenhigher losses in future period 2 (2041–2070). Within the herbaceous crops, sunflower and winter wheatwere the most susceptible to yield losses under climate change, reaching estimated maximum lossesfor future period 2 of respectively 18.5% and 13.6%, followed by natural grown pastures with 11.5%.For woody crops, maximum estimated yields losses were considerably higher for almond (27.2%) thangrapevine (5.4%) and olive (14.9%).